The Relationship Between Low Purine Diet Compliance with the Incidence of Gout Arthritis in the Elderly in Tinelo Village Working Area of Telaga Biru Health Center - Hamna Vonny Lasanuddin; Haslinda Damansyah; Pujiati Pujiati (Universitas Ibn Khaldun Bogor, 2024)
Gout arthritis occurs due to triggers, such as foods and other compounds that contain excessive purines. Based on data from the Regional Basic Health Research of Gorontalo Province, the total number of joint diseases in Gorontalo is ranked 16th out of 34 Provinces and based on diagnoses for ages 45-54 years reaches 11.1%, ages 55-64 years reach 15.5%, and ages 65-74 years reach 18.6% with the highest total number dominated by women 8.5% compared to men 6.1%. This study was conducted to determine the relationship between low-purine diet adherence and the incidence of gout arthritis in the elderly in Tiello Village. This study is an observational analytical study with a cross-sectional approach, using questionnaire measuring instruments and then statistical analysis using a chi-square test with a meaning level of α=0.05. The population in this study was all elderly people with gout arthritis in Tinelo Village with a total of 70 people. This study used a Purposive sampling technique with a total sample in this study was 42 people. This study shows that there is a significant relationship between a low-purine diet and the incidence of gout arthritis in the elderly in Tinelo Village, Telaga Biru Health Center Working Area with a value of ρ=0.001 smaller than the value of α=0.05. There is a significant relationship between a low-purine diet and the incidence of gout arthritis in the elderly in Tinelo Village, Telaga Biru Puskemas Working Area.